The Analysis of Generation Z's Perception in Decisions on Selection of Islamic Banking Service - Moch. Rusli (Riwayat: Educational Journal of History and Humanities, 2023)
Islamic Banking as an alternative financial institution for the community and its current condition is growing. Likewise with some sharia products offered began to adjust to the needs of the community. Given that most of Indonesia's population is Muslim, the potential for the development of Islamic banking is also quite large. Islamic banking should be able to develop more broadly to demonstrate sharia values reflected in law, economic, social and political institutions. The Islamic banking system is expected to apply Islamic economic rules to avoid the conventional system to conform to Islamic religious teachings. The development of Islamic banking customers today not only targets the worker segment but also targets generation Z, the majority of whom this year work as students. The current condition of Islamic banking is unknown among generation Z, so it is necessary to analyze what factors influence the selection of Islamic banking as a financial institution to facilitate economic activities. The results of the analysis can be formulated to carry out strategies related to marketing, operations, risk, and finance in carrying out activities. In answering this, research was conducted using quantitative methods using multiple linear regression which aimed to see psychological, cultural, social, personal, and marketing factors in relation to the selection of Islamic banking. The results showed that partially psychological factors, social factors, personal factors and marketing factors had a positive effect on variable Y, namely the selection of Islamic banking services generation Z and factor X represented by cultural factors had a negative influence not significantly.